Empowering Supply Chain Literacy Through Sustainable Innovation Education: A Community-Based Approach - Nurprihatin, Filscha; Khairunnisa, Rifa Nur; Luin, Julliete Angel; Mardhatillah, Nur Rizka (Journal of Community Services: Sustainability and Empowerment, 2025)
This paper presents a community service initiative designed to enhance supply chain literacy through a workshop titled "Global Networking: Sustainable Innovation in Supply Chain." The activity, held in October 2024, targeted undergraduate students and young professionals in logistics and operations management, with a focus on omnichannel strategies, procurement innovation, and sustainability. The community's need stemmed from limited exposure to current trends in supply chain innovation and the increasing demand for competencies aligned with green and digital transformation. The service was structured around interactive sessions, case study discussions, and participant feedback. Outcomes demonstrated improved understanding of sustainable practices, increased awareness of procurement partnerships, and stronger participant engagement. Reflections reveal the potential scalability of this model to other institutions and local communities. The program contributes not only to knowledge dissemination but also to sustainable human capital development in the logistics sector.